You're stronger than you think The power to do what you feel you can't - Parrott, Les (Carol Stream Tyndale House Publishers, Inc., 2012)
The secret to tapping into your inner strength is not positive thinking of pulling yourself up by your bootstraps. It's leveraging the surprising inner power of your mind, heart, and soul. Access the power to do what you feel you can't with practicality
Keywords: Self-realization -- Religious aspects -- Christianity. Christian life. RELIGION -- Christian Life -- Spiritual Growth. RELIGION -- Christian Ministry -- Discipleship